Effect of weekly training frequency with the Nordic Hamstring Exercise on muscle-strain risk factors in football players: A randomized trial - Medeiros, T. M.; Ribeiro-Alvares, J. B.; Fritsch, C. G.; Oliveira, G. S.; Severo-Silveira, L.; Pappas, E.; Baroni, B. M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the differences between performing Nordic hamstring exercises once or twice a week on hamstring eccentric strength and other muscle-strain risk factors in high-level football players.